Effect of the PROFIT-BR exercise program on physical fitness of children: a protocol study - Augusto Pedretti; Adroaldo Cezar Araujo Gaya; Júlio Brugnara Mello; Anelise Reis Gaya (BMC, 2024)
Abstract Background Considering that school environments are important and have the potential to promote an active lifestyle with direct impacts on physical, motor, cognitive, affective, and psychological aspects, the objective of this study was to evaluate the effect of a physical exercise program in the school context. Methods A parallel, two-arm experimental research project carried out over 19 weeks, with two non-consecutive weekly classes of 60 min, with the inclusion of PROFIT-BR in the initial 15 min of the class followed by 40 min based on specific physical education skills on indicators of physical fitness in children. Estimates of excess weight and visceral fat will be measured and assessed by body mass index and waist-to-height ratio, respectively, and cardiorespiratory fitness by performance in the six-minute run/walk test. Flexibility will be assessed by the sit and reach test; and muscle strength measured by the number of sit-ups in one minute. The 2 kg medicine ball throw and the horizontal jump will be used to measure upper and lower limb power, respectively, the square test used as a measure of agility, and the 20-meter run test used to measure speed. To analyze the differences between baseline and post-intervention values, repeated measures ANOVA adjusted for somatic maturation will be used. The magnitude of the effect size will be estimated by "partial eta squared". Statistical analyses will be carried out using SPSS version 24.0 software and a 5% probability of error in the analyses will be accepted. Discussion The main theoretical assumption of the proposal is the cause-and-effect relationship between the regular practice of physical exercise in childhood and adolescence and several parameters of health and motor performance. The elaborated program has a lot of applicability because it was wondering from the perspective of the school, in terms of materials, space, and objectives of physical education.